Intelligent and Robust Control of Dual Stage Actuator Arm using GA based Fixed Structure Robust Loop Shaping Control - Kaitwanidvilai, S.; Nath, A. (Applied Science and Engineering Progress, 2013)
Since the aerial density of Hard Disk Drive (HDD) is increasing at very impressive rate, conventional techniques for controlling HDD servo system can no longer meet the necessary tracking performance and robustness; a new class of servo controller will be required to address this issue. H∞ robust controller is one of the most popular techniques for designing a robust controller and it provides necessary robustness and performance even under perturbed plant conditions. However, the order of controller designed by this technique is usually higher than that of the plant, making it difficult to implement practically. To overcome this problem, this paper proposes a new technique for designing a robust controller for HDD with Voice Coil motor (VCM) and micro actuator called dual stage actualtor. The proposed technique does not only solve the problem of complicated and high order controller but also still retains the robust performance of conventional H∞ control technique. Simulation results show the effectiveness of our proposed technique